Factorial models to estimate isoleucine requirements for broilers - Melaré, Mirella Cunha [UNESP]; Sakomura, Nilva Kazue [UNESP]; Reis, Matheus de Paula [UNESP]; Peruzzi, Nelson José [UNESP]; Gonçalves, Camila Angélica [UNESP] (Wiley, 2019)
The objective of this work was to determine the efficiency of utilization (EU) and produce factorial models for optimal isoleucine (Ile) intake. Six dose–response trials were carried out, three for males and three for females, with 640 Ross 308 in each studied phase. The initial (1–14 days), grower (15–28 days) and finisher (29–42 days) phases were evaluated to cover the growing phase of the broiler chicken. In total, eight treatments were randomly distributed to four replicates of 20 birds each. The treatments consisted of seven crescent levels of Ile and one counter proof to ensure that Ile was the first limiting amino acid in the diet. Dilution technique was applied to produce the levels of Ile and keep the amino acid ratio with lysine. The EU was determined to account for whole body or partitioned for feather-free body (Bff) and feather. Two distinct factorial models were adjusted, M1 and M2. The M2 model was evaluated for one or two EU, being denominated as M2 and M3. When the efficiency was partitioned, the values of 53% and 69% for feather and Bff were determined. The optimal Ile intake estimated for each model were of 275, 908, 1,412 mg of Ile/bird/day (M1); 258, 829, 1,321 mg of Ile/bird/day (M2); and 284, 835, 1,288 mg of Ile/bird/day (M3) for initial, grower and finisher phases respectively. The EU partitioned for feather-free body and feather reduced the biased of the model M3. Overall, higher values of Ile intake are estimated when model M1 is used, which may be the difference in account for body weight gain (M1) or only protein gain (M2 and M3) to estimate the amount of amino acid required for broiler.
Keywords: efficiency of utilization; isoleucine; mathematical modelling